Industrial finance in India : a study in investment banking and state-aid to industry with special reference to India - Basu, Saroj Kumar (Calcutta : University of Calcutta, 1961)
The study is an attempt at a survey and solution of the main problem, of industrial finance in India. The principal agencies for the supply of industrial finance in the country have been analysed and the part played by each of these factors in the provision of industrial finance has been carefully examined, among these factors the managing agents play as important a part and constitute so unique a feature of India$1 (Bs business organisation that a detailed consideration of the agency system in all its aspects has been necessary.s
Includes index.
Includes bibliographical reference: p. 477-488.
uaa 24/01/2017
Loans.
Keywords: Industrial policy; Corporations--Finance; Banks and banking; Industries; Investment banking; India